Fishing for growth : export-led development in Peru, 1950-1967 - Roemer, Michael (Cambridge, Mass. : Harvard University Press, 1970)
The aim of the author was not only to complete a case study that would put export-led development in a favourable light, but also to draw some practical conclusions for other developing countries which must depend on primary exports to propel development.
A revision of the author's thesis, Massachusetts Institute of Technology.
Includes index.
Including bibliographical references: p. 193-200.
osa 23/01/2019
Loans
Keywords: Fish meal; Peru